Mock the Week's Funniest Book of All Time - Phillips, Ewan [ et al.] (London Boxtree, 2011)
Mock the Week's Funniest Book of All Time is an hilarious, edgy collection of brand new gags from the team behind the popular panel show.
Include Illustration and Maps
Keywords: Mock the week (Television program) -- English wit and humor